ADSC-derived exosomes mitigate radiation-induced skin injury by reducing oxidative stress, inflammation and cell death - Liu, Zhe; Gu, Jiawei; Gao, Yakun; Hu, Hao; Jiang, Hua (Frontiers in Public Health, 2025)
BackgroundRadiation-induced skin injury (RISI) is a significant complication of radiotherapy and affects over 95% of patients who undergo radiation treatment. The pathophysiological cascade of RISI includes oxidative stress, persistent inflammation, and excessive fibrotic remodeling. Current treatments provide limited efficacy and primarily focusing on symptomatic relief. Exosomes from adipose-derived stem cells (ADSC-Exo) offer promising therapeutic effects on multiple types of skin injury, while their roles in the treatment of RISI remains to be fully explored.MethodA mouse model of RISI and an in vitro radiation-induced cellular damage model were established to evaluate the therapeutic effects of ADSC-derived exosomes. ADSC-Exo were isolated via size-exclusion chromatography and characterized using TEM, NTA, and immunoblotting. H&E staining and Masson staining were used to evaluate the extent of skin radiation-induced skin damage and fibrosis. Skin immunofluorescence was performed to assess macrophage infiltration and polarization, while immunohistochemistry staining was conducted to determine the expression levels of inflammatory mediators in the skin samples. In the in vitro experiments, ROS probes were used to evaluate cellular oxidative stress levels, and western blot analysis was employed to detect the expression levels of apoptosis and pyroptosis related proteins.ResultADSC-Exo effectively alleviated radiation-induced skin injury and fibrosis, reduced macrophage infiltration, and promoted macrophage polarization toward the M2 phenotype. Additionally, ADSC-Exo decreased the expression levels of IL-1β and IL-6 in skin tissues after irradiation. In in vitro experiments, ADSC-Exo mitigated oxidative stress in irradiated mouse fibroblasts, and reduced the upregulation of apoptosis-related proteins BAX and CASPASE-3, as well as pyroptosis-related proteins GSDMD and CASPASE-1 after radiation exposure.ConclusionADSC-Exo alleviated RISI through multifaceted effects, including macrophage polarization modulation, inflammation suppression, oxidative stress reduction, and inhibition of apoptosis and pyroptosis. These findings support the potential of ADSC-Exo as a promising cell-free therapy for RISI.